The EU-US Relations in An Emerging Multipolar World - Roxana Hincu (CES Working Papers, 2014)
In the context of an emerging multipolar world, the transatlantic partnership faces various challenges in the attempt to maintain the Western-shaped and dominated liberal order. This article aims to synthesize and rationalize the central argumentative positions on the ever-evolving transatlantic relationship provided by the following theories of international relations: neorealism, neoliberalism and constructivism. A combination of the main assumptions of the three approaches brings useful insights into the policy debates on the role of the transatlantic partnership in the process of forging the global governance. Nevertheless, where the systemic theories such as neorealism and neoliberalism fall short in explaining the transatlantic relations, constructivism, with its focus on actor identity succeeds in offering a dynamic account of them.
Keywords: C01; 330; transatlantic partnership; security; neorealism; neoliberalism; constructivism; multipolarity; global governance Romania